(untitled) (Eurasian Medical Research Periodical, 2022)
This article talks about diseases of the mucous membrane of the oral cavity and modern methods of treatment. The classification of diseases of the oral mucosa helps to make the correct diagnosis and start therapy in a timely manner, preventing more serious negative consequences.